The Moderation Effect of Digital Transformation on the Influence of Effectiveness and Quality of Service on Public Service User Satisfaction in South Sulawesi - Reynilda; Kamaluddin, La Ode Amijaya; Ali, Muh. Akbar; Khatimah, Husnul (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Technological advances in the era of disruption have penetrated various fields including public management which is closely related to the needs of the community. This study aims to determine the effect of effectiveness on user satisfaction, the effect of service quality on user satisfaction, and the role of technological transformation as a moderator related to the relationship between effectiveness and service quality on user satisfaction in the public sector. The research method applies a quantitative method using a moderated regression model. Data collection was carried out using questionnaires at one-stop service offices (public service malls) in three municipalities in South Sulawesi, namely Makassar City, Pare-Pare City, and Palopo City with a sample size of 90 people. The results of the study indicate that effectiveness and service quality partially have a significant and positive effect on user satisfaction of public services. Digital transformation shows its role as a significant moderating variable in the relationship between effectiveness and quality of public services on user satisfaction of public services